2011
DOI: 10.1111/j.1467-9361.2011.00606.x
|View full text |Cite
|
Sign up to set email alerts
|

Political and Fiscal Risk Determinants of Sovereign Spreads in Emerging Markets

Abstract: Using a panel of 46 emerging market economies from 1997 to 2008, this paper investigates the key determinants of country risk premiums as measured by sovereign bond spreads. Unlike previous studies, the results indicate that both political and fiscal factors matter for credit risk in emerging markets. Lower levels of political risk are associated with tighter spreads, particularly during financial turmoil. Efforts at fiscal consolidation narrow credit spreads, especially in countries with high initial public d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 40 publications
3
59
0
Order By: Relevance
“…Hilscher and Nosbusch (2010) empirically examine this relationship and find that the terms of trade as well as the volatility of the terms of trade are significant factors affecting sovereign spreads for 31 emerging economies. Min (1998), Baldacci et al (2011) and Gibson et al (2012) among others, also report that the terms of trade have a significant, inverse relationship with sovereign spreads.…”
Section: Macroeconomic Determinantsmentioning
confidence: 86%
“…Hilscher and Nosbusch (2010) empirically examine this relationship and find that the terms of trade as well as the volatility of the terms of trade are significant factors affecting sovereign spreads for 31 emerging economies. Min (1998), Baldacci et al (2011) and Gibson et al (2012) among others, also report that the terms of trade have a significant, inverse relationship with sovereign spreads.…”
Section: Macroeconomic Determinantsmentioning
confidence: 86%
“…Gonzalez-Rozada and Levy-Yeyati (2008) find that the long-term foreign debt S&P ratings have explanatory power for spreads in 33 emerging economies. Baldacci et al (2011) employ a measure of political risk which is based on the Heritage Foundation economic freedom index and the World Bank governance index. They also find that political risk is an important determinant of spreads.…”
Section: Solvency Liquidity and Other Factorsmentioning
confidence: 99%
“…The most commonly used global variables in empirical bond and CDS spread studies are the VIX index, which proxies for volatility in global markets, the yield on a long-term US Treasury bond, which proxies for changes in the US economy, the default yield spread defined as the spread between corporate bonds with low and high credit rating, the returns on a US stock market index, which proxies for the global economic condition and the global business cycle, the TED spread, which proxies for changes in global liquidity, and an equity risk premium proxy, such as the earnings price ratio on a stock market index (see, for example, Longstaff et al, 2011;Gonzalez-Rozada and Levy-Yeyati, 2008;Hilscher and Nosbusch, 2010;Baldacci et al, 2011;Beck, 2001;Eichengreen and Mody, 2000).…”
Section: Longstaffmentioning
confidence: 99%
“…Previous studies have shown that the consequences of political risk differ from one African market to another and have influenced the types of international strategy that firms adopt (Baldacci, Gupta, & Mati, 2011). This means that each African market has specific political risk that differentiates one from another, therefore creating different scenarios for MNCs to assess (Bekaert et al, 2014;Quer, Claver, & Rienda, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Sub-Saharan Africa is regarded as high risk, but there are significant intercountry variations in risk perception versus actual risk. Likewise, MNCs have specific characteristics that cause them to perceive political risk differently (Baldacci et al, 2011;Bekaert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%